Influence of collagen fibre orientation on the frictional properties of articular cartilage. Issue 2 (5th May 2021) - Yarimitsu, Seido; Ito, Kei; Fujie, Hiromichi
Abstract: Articular cartilage has a unique collagen fibre network structure that exhibits both anisotropy and depth dependency. Collagen fibre orientation in a cross‐section parallel to the articular cartilage surface may affect the lubrication properties of articular cartilage. The effect of collagen fibre orientation on the frictional properties of articular cartilage was examined through finite element analysis of the friction. Specifically, a three‐dimensional fibre‐reinforced poroelastic biphasic model was used to determine the influence of collagen fibril orientation on the frictional properties of articular cartilage. The simulations reveal that collagen fibre orientation has a significant influence on the deformation behaviour of articular cartilage in front of and behind the contact area. The coefficient of dynamic friction was lower in the direction parallel to the collagen fibre orientation than in the direction perpendicular to the collagen fibre orientation, regardless of the indenter speed.